Analisis Kelembagaan Perkebunan Kelapa Sawit Rakyat Pola Plasma Menghadapi Pasar Global di Kecamatan Ukui Kabupaten Pelalawan - Masa Derita Ndraha; Sakti Hutabarat; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Development of oil palm plantation creates positive and negative impacts to people, environment and economy. Growing awareness of global consumens on sustainable oil palm production provokes some international institutions to establish standards and certification. The role of institutions in palm oil supply chain become an important issue to assure that the process of palm oil production is tracable. The objective of this study is to identify various institutions in oil palm supply chain and analyse the role of relevant institutions in scheme smallholders level such as access inputs, access financial, access market, access information and technology, access land title, and access institutional. The study used descriptive qualitative methods to figure out market coordination in the oil palm market. Data were collected from sample farmers and manager of each institutions. The results show that there are various institutions involve in oil palm supply chain at scheme smallholders including cooperatives, millers, local government, banks, local trader, and NGO. The institutions have different roles in the oil palm supply chain to produce sustainable oil palm production under RSPO certification. Keywords: Scheme smallholdes, Institutions, Global market, Certification